Microarray of Recombinant Antibodies Using a Streptavidin Sensor Surface Self-Assembled onto a Gold Layer - P. Pavlickova; A. Knappik; D. Kambhampati; F. Ortigao; H. Hug (BioTechniques, 2003)
We have developed a sensitive method for the detection of recombinant antibody-antigen interactions in a microarray format. The biochip sensor platform used in this study is based on an oriented streptavidin monolayer that provides a biological interface with well-defined surface architecture that dramatically reduces nonspecific binding interactions. All the antibody or antigen probes were biotinylated and coupled onto streptavidin-coated biochip surfaces (1 μL total volume). The detection limits for the immobilized probes on the microarray surface were 0.5 μg/mL (200 fmol/spot) for the peptide antigen and 0.1 μg/mL (3 fmol/spot) for the recombinant antibodies. Optimal concentrations for the detection of the Cy5-labeled protein target were in the range of 20 μg/mL. Protein microchips were used to measure antibody-antigen kinetics, to find optimal temperature conditions, and to establish the shelf life of recombinant antibodies immobilized on the streptavidin surface. For recombinant antibody fragments with a kDa of 10–100 nM, we have established an easy and direct immunoassay. In addition, we developed an indirect method for antibody detection with no need for expensive and time-consuming antibody purifications and modifications. Such a method was shown to be useful for large-scale screening of recombinant antibody fragments directly after their functional expression in bacteria. Our data demonstrate that recombinant antibody fragments are suitable components in the construction of antibody chips.